Conspecific pollen advantage mediated by the extragynoecial compitum and its potential to resist interspecific reproductive interference between two Sagittaria species - Fei, Cai-Hong; Tang, Sha-Sha; Shang, Shu-He; Dai, Jie; Wang, Xin-Yi; Wang, Shuai; Liu, Wei-Qi; Wang, Xiao-Fan (Frontiers in Plant Science, 2022)
The extragynoecial compitum formed by the incomplete fusion of carpel margins, while allowing intercarpellary growth of pollen tubes in apocarpous angiosperms, may also increase the risk of reproductive interference caused by heterospecific pollen (HP) deposition. In Sagittaria, congeneric HP tubes grow via different paths and enter the ovules later than conspecific pollen (CP) tubes. However, it is unclear how the growth advantage of the CP tube helps ensure reproductive success when HP is deposited on the stigmas. We performed molecular characterization of interspecies-pollinated seeds to examine the consequences of interspecific pollen deposition between Sagittaria pygmaea and Sagittaria trifolia. We also conducted CP–HP (1:1) mixed pollination and delayed CP pollination treatments to explore the seed-siring abilities of CP and HP. Our results showed that although HP could trigger the development of fruits, the interspecies-pollinated seeds contained partially developed embryos and could not germinate. More than 70% of the embryos in these seeds were molecularly identified as hybrids of both species, suggesting that HP tubes could enter the ovules and fertilize the egg cells. Moreover, CP could sire more offspring (≥70%) after the CP–HP (1:1) mixed pollination treatment, even when HP reached the stigma 0.5–1 h earlier than CP (≥50%). Following adequate CP versus HP (1:1) pollination on carpels on two sides of the apocarpous gynoecium, both species produced >70% conspecific seeds, indicating that the CP tubes could occupy ovules that should be occupied by HP via the extragynoecial compitum. Our results reveal that in Sagittaria, pollen deposition from co-existing congeneric heterospecies leads to interspecific seed discounting. However, the CP advantage mediated by the extragynoecial compitum is an effective strategy to mitigate the effects of interspecific pollen deposition. This study improves our understanding of how apocarpous angiosperms with an extragynoecial compitum can maintain species stability and mitigate the negative reproductive interference effect from sympatrically distributed related species.